Foreign Branding and Its Effect on Brand Perception: an Overview to Local Entrepreneurs - Rizky Vita Losi; Ahmad Fadlan; Putri Selviani (Neo Journal of economy and social humanities, 2023)
Foreign branding is a branding strategy by giving a brand name using spelling or pronunciation in a certain foreign language, with the main target of influencing the dimensions of brand image, and influencing perceived quality, as well consumer attitudes towards products. The purpose of this research is to explain foreign branding and its effect on brand perception. A literature review from various sources related to foreign branding strategy was conducted as part of the research. According to the research findings, brand image, purchase decision, and brand admiration are the effects of foreign branding. Consumers tend to prefer foreign-sound products because it creates brand image as international products which have best quality. So it effects on how people decide to but the foreign products and people also admire foreign-sound products too much especially in young generation. Local entrepreneurs should learn a lot about foreign branding to compete and upgrade the level of their products and sales.